2007
DOI: 10.5194/angeo-25-1779-2007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variations of the mesospheric wind field at mid-latitudes

Abstract: Abstract. Continuous MF radar observations at the station Juliusruh (54.6 • N; 13.4 • E) have been analysed for the time interval between 1990 and 2005, to obtain information about solar activity-induced variations, as well as long-term trends in the mesospheric wind field. Using monthly median values of the zonal and the meridional prevailing wind components, as well as of the amplitude of the semidiurnal tide, regression analyses have been carried out with a dependence on solar activity and time. The solar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 27 publications
(75 reference statements)
9
76
0
Order By: Relevance
“…In future studies, the momentum balance should also be estimated and discussed for similar radar instruments at other latitudes, like the MF radar at the midlatitude site Juliusruh (see, e.g., Keuer et al, 2007). This would allow the definition of the time and height range where the mainly GW-determined momentum balance is fulfilled for different latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, the momentum balance should also be estimated and discussed for similar radar instruments at other latitudes, like the MF radar at the midlatitude site Juliusruh (see, e.g., Keuer et al, 2007). This would allow the definition of the time and height range where the mainly GW-determined momentum balance is fulfilled for different latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, with the measurements available today, it is not possible to determine definitively to what extent observed changes in gravity waves are due to filtering by middle atmosphere winds and to what extent changing sources or other changes in local conditions contribute. Jacobi et al (2012) and Keuer et al (2007) also reported on NH midlatitude MLT wind trends. Jacobi et al (2012) noted the differences in the trends between North America and Europe, suggesting that changes in planetary waves contributed to the trends.…”
Section: Long-term Trendsmentioning
confidence: 99%
“…Figure 2 indeed shows such a connection for solar maximum. During solar maximum, mesospheric eastward winds are stronger, leading to a negative correlation between solar flux and mean wind there (e.g., Keuer et al, 2007). However, stronger winds and consequently larger GW amplitudes lead to a stronger GW drag, stronger wind shear, and therefore a decreasing solar cycle effect on the mean wind with height, which reverses at some altitude.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, search for an effect of the 11-year solar Schwabe cycle has been undertaken, for example, to explain part of the observed variability of mesosphere and lower thermosphere (MLT), which can be studied by radars. Indeed, indication for a solar effect has been found in MLT radar wind time series over Central Europe Keuer et al, 2007). This effect is more pronounced in summer than in winter owing to the more disturbed middle atmosphere during winter, and essentially consists in a stronger mesospheric jet during solar maximum.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation